CALPHAD and rule-of-mixtures: A comparative study for refractory high entropy alloys. (December 2020) - Shaikh, Sufyan M.; Hariharan, V.S.; Yadav, Satyesh K.; Murty, B.S.
Abstract: Present work studies 126 quaternary and 126 quinary equiatomic refractory high entropy alloys (RHEAs), made from Group IV (Ti, Zr, Hf), Group V (V, Nb, Ta) and Group VI (Cr, Mo, W) elements. Rule-of-mixtures (ROM) technique is used to calculate liquidus temperature, density (ρ), Young's modulus (E), % atomic size difference (δ), valence electron concentration (VEC) and specific heat at constant pressure and at 1273 K ( C p ). CALPHAD technique is used to predict the number of phases formed at 298 K, ρ and liquidus temperature. ROM calculated densities are matching perfectly with CALPHAD values. Densities and E are directly proportional to the VEC and liquidus temperature of the alloys. Ti, Zr, Hf are ductilizing the alloys and making them light; whereas Cr, Mo and W, are reducing the alloys' ductility and making them heavy. For quinary RHEAs, C p shows six distinct groups with δ, but a similar trend is not observed in quaternary RHEAs. A methodology is developed to screen a large number of alloys based on various properties. Correlations between those properties are also studied. Graphical abstract: Image 1 Highlights: 252 equiatomic alloys made from Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, are studied. None of the equiatomic quinary alloys has single phase at 298 K. Ti, Zr, Hf are ductilizing the alloys while Cr, Mo, W, are decreasing the ductility. Cp shows six distinct groups when plotted against % atomic size difference. VEC and melting point are strongly influencing Young's modulus and density.